O discurso musical Rap: expressão local de um fenômeno mundial e sua interface com a educação - Macedo, Iolanda (2010)
This study aims at examining the educational processes that are inherent to hip hop. This cultural movement emerged in the United States, created primarily by young people from African American and Latin American communities in the suburbs of New York city in the late 1970s. Four elements are present in the constitution of hip hop: the DJ, MC, breaking and graffiti writing; later, knowledge was included as another element. The performance of the DJ and the MC originates the rap genre. This musical genre is widely consumed, mainly by young people from many countries, since the rap style has gone through a process of globalization, in which the cultural industry, especially the North American one, played a key role. The movement has complex roots and, consequently, presents a heterogeneous context. In this sense, even though hip hop is related to a common collective universe, in the emergence of the street culture, it presents conflicts and contradictions, as in any other community. The hip hop movement came to Brazil through the media, but we consider that this transposition process was not based solely on the passive consumption, but on its reappropriation. This way, Brazilian hip hop is constituted as a local expression of a worldwide phenomenon. Rap, besides being a musical genre consumed by young people from the Brazilian suburbs, is also a generator of meanings, and its musical discourse is characterized as one of the stages of this production. Thus, besides listening to the songs, the public also wants to know who make them, and what their opinions, ideas and understanding of reality are. This production of meaning also permeates an aesthetic, behavioral, political and ideological construction. In order to explain such debate, we also use the concept of identity. The understanding of the educational processes intrinsic to rap is mainly due to the understanding of education in its broadest sense. In this sense, we consider that rap, as an deliberate musical discourse, propitiates a process of informal education. We aim at identifying in Brazilian rap, in which crime and violence are prevalent in the presentation of discourse, how the rappers try to convince the public to share a certain understanding of the historical reality, in particular the economic and social segregation experienced in the suburbs. Through this discourse and informal educational act, the rappers also aim at stimulating a change of behavior in his listeners, trying to lead them to participate of their action strategy towards a social change.